The Effects of Chronic Ethanol Self-Administration on Hippocampal Serotonin Transporter Density in Monkeys - Burnett, Elizabeth J.; Davenport, April T.; Grant, Kathleen A.; Friedman, David P. (Frontiers in Psychiatry, 2012)
Evidence for an interaction between alcohol consumption and the serotonin system has been observed repeatedly in both humans and animal models yet the specific relationship between the two remains unclear. Research has focused primarily on the serotonin transporter (SERT) due in part to its role in regulating extracellular levels of serotonin. The hippocampal formation is heavily innervated by ascending serotonin fibers and is a major component of the neurocircuitry involved in mediating the reinforcing effects of alcohol. The current study investigated the effects of chronic ethanol self-administration on hippocampal SERT in a layer and field specific manner using a monkey model of human alcohol consumption. [3H]Citalopram was used to measure hippocampal SERT density in male cynomolgus macaques that voluntarily self-administered ethanol for 18 months. Hippocampal [3H]citalopram binding was less dense in ethanol drinkers than in controls, with the greatest effect observed in the molecular layer of the dentate gyrus. SERT density was not correlated with measures of ethanol consumption or blood ethanol concentrations, suggesting the possibility that a threshold level of consumption had been met. The lower hippocampal SERT density observed suggests that chronic ethanol consumption is associated with altered serotonergic modulation of hippocampal neurotransmission.